2003
DOI: 10.1002/app.12717
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependency of elastic moduli and internal dilational and shear frictions of polyetherimide

Abstract: ABSTRACT:To investigate the thermally activated structural change of polyetherimide, longitudinal and transverse wave velocity, six kinds of elastic parameters (Young's, shear, and bulk moduli, Lamé parameter, Poisson's ratio, and Debye temperature), and dilational and shear internal frictions were simultaneously measured over a temperature range 69 -474 K, using the ultrasonic pulse method. All elastic moduli decreased with increasing temperature, suggesting a lowering of molecular bonding strength. From shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…In addition, generally the glass transition occurs from T g -50 K for bulk polymers. Therefore, E bulk ( T ) for bulk PS at T < T g -50 K is a linear function, which can be deduced from the experimental data obtained from E bulk ( T ) = -0.00189 T + 4.558 [19]. The result is also in agreement with another experimental result where the elastic modulus of bulk PS, E bulk = 4.0 GPa at T = 294 ± 3 K [12].…”
Section: Resultssupporting
confidence: 87%
“…In addition, generally the glass transition occurs from T g -50 K for bulk polymers. Therefore, E bulk ( T ) for bulk PS at T < T g -50 K is a linear function, which can be deduced from the experimental data obtained from E bulk ( T ) = -0.00189 T + 4.558 [19]. The result is also in agreement with another experimental result where the elastic modulus of bulk PS, E bulk = 4.0 GPa at T = 294 ± 3 K [12].…”
Section: Resultssupporting
confidence: 87%
“…The C O group becomes progressively stretched through mechanical shear stresses and minor heating of the sliding surface, determining the polymer chain mobility. Fukuhara [8] investigated the thermally activated structural changes in polyetherimide by internal friction and also concluded that relaxation induced important C O motions. However, the relative intensity remains constant at 140-180…”
Section: Surface Characterisation Raman Spectroscopymentioning
confidence: 99%
“…The imide I band intensifies as a function of bulk temperatures at 50 N. The C --O group becomes progressively stretched through shear stresses and minor heating of the sliding surface, determining the polymer chain mobility. Fukuhara et al [107] investigated the thermally activated structural changes in poly(ether imide) by internal friction and also concluded that relaxation induced important C --O motions. However, the relative intensity remains constant at 140 to 180 8C sliding temperatures because the previously detailed hydrolysis reactions restrict the molecular mobility in this temperature range.…”
Section: Sintered Polyimidementioning
confidence: 99%